2012
DOI: 10.1016/j.ijscr.2012.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized cellulose (Surgicel) based reaction post thyroidectomy mimicking an abscess: A case report

Abstract: We present the first head and neck reaction to oxidized cellulose. This report serves to remind head and neck surgeons of the potential for local tissue reactions to this material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Royds et al [ 36 ] documented the first case of local tissue reaction associated with Surgicel ® in head and neck surgery, with removal and resolution confirming its cause. Concha et al [ 37 ] reported a case of xanthogranulomatous pyelonephritis caused by OC retention in a renal allograft, with consequent extirpation of the allograft and return to dialysis in a 41-year-old patient.…”
Section: Discussionmentioning
confidence: 99%
“…Royds et al [ 36 ] documented the first case of local tissue reaction associated with Surgicel ® in head and neck surgery, with removal and resolution confirming its cause. Concha et al [ 37 ] reported a case of xanthogranulomatous pyelonephritis caused by OC retention in a renal allograft, with consequent extirpation of the allograft and return to dialysis in a 41-year-old patient.…”
Section: Discussionmentioning
confidence: 99%
“…They are designed to be left in situ after surgery. Reported events after the use of OCHAs may be broadly grouped into 3 categories: direct mass effects [5] , granuloma formation sometimes mimicking tumours [6] and pseudoabscess [7] . An earlier prospective study of Gelita-Cel OCHAs administered at mediastinoscopy suggested that the material was absorbed by day 14 [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of surgicel as a hemostatic agent include its inertness, bio absorbability, no foreign body reaction and in-vitro antibacterial effects 67. Nevertheless literature suggests that surgicel can swell and increase in volume following saturation with blood thereby leading to mechanical compression on vital anatomical structures and radiographic artefacts mimicking abscesses and tumors in CT and ultrasonography 6202122232425…”
Section: Discussionmentioning
confidence: 99%